Polarized pasts : heritage and belonging in times of political polarization - Niklasson, Elisabeth (Explorations in heritage studies, 2023)
"When questions of belonging enter the forefront of political debates, so too does heritage. From different ends at the political spectrum, people invoke the past to validate their stance on immigration, equality and security. In the wake of European crises and a polarized US political landscape, heritage is invoked to both halt and embrace immigration, as well as to resist and further globalization. Essays demonstrate how ancient monuments and sites, bygone eras and political regimes, even your genetic ancestry, can become wrapped up in polarized political debates. Together, the texts pave the way for a better understanding of the role of the heritage in society"--